Design and study of a laser system for detecting optical devices - Hnatenko, O. S.; Machekhin, Yu. P.; Neofitnyi, M. V.; Gulak, S. V. (ХНУРЭ, 2019)
The development of a laser system for detecting optical devices is presented in this research work. The proposed laser system is based on two principles: first, fixing glare from optical devices; second, fixation with the help of a high-sensitive photodiode of low-intensity emission, which in turn complicates the operation of counteraction systems offered for the laser system.
Keywords: laser system; detecting; optical devices